Internet access and cardiovascular death in the United States - Jeffrey B. Moorhead, Jr; Brandon M. Herbert; Kaleab Z. Abebe; Christina Harrington; Elizabeth Miller; Stacy T. Lindau; Jared W. Magnani; Amber E. Johnson (American Heart Journal Plus, 2022)
As high-speed internet becomes increasingly important as a resource for cardiovascular disease (CVD) prevention and management services, gaps in digital infrastructure may have detrimental impact on health outcomes. Using national census and CDC data from 2018 we evaluated state-level rates of household internet access and age-adjusted cardiac mortality. After adjusting for state level demographic variables, and rates of education, income, and health insurance, internet access rates were inversely associated with age adjusted CVD mortality, showing that the potential for internet access to affect CVD management deserves further study.